Discourse Analysis Of Gettysburg Address - Yanuarius Yanu Darmawan (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
Text is a common instrument in delivering a language from the first person (addresser) to the second person (addressee). However, different text means different purpose. A political speech text is such an example. It can function as a political agreement between two countries, or it can be as a letter of a world peace arrangement, such as Gettysburg Address. This political speech was made along time ago in America by President Abraham Lincoln to set peace that was longed for by the northern side (The Union) and the southern side (The Confederacy). In a deeper look of the text, it is more than just a text of peace proposal. The content, which is divided into three divisions, gave the positive result for the unity of the separated nation at that time. The successful delivering of the speech makes this text is worth to be analyzed. The study will concern only about the theme of the text and the intended meaning of the speech which is based on historical background of this political speech. The organization of the text itself is seen from the transitivity study. Still, there are many things to be analyzed based on the sentences of each division of the text.